Willingness of Employers to Hire Ex-Convicts in Private Institutions: A Basis for Non-Discriminatory Hiring Guideline Handbook in Employing Ex-Convicts - Alolor, Mavelaine L.; Elman, Mikka F.; Dindang, Ronairah D. (International Journal of Research in Interdisciplinary Studies, 2025)
This study explores the willingness of employers to hire ex-convicts, a crucial aspect of their reintegration into society. Factors influencing employers' willingness include the nature of the crime, the time elapsed since the conviction, and the individual's rehabilitation efforts. Studies indicate that educational and vocational training programs, along with government incentives, can positively impact employers' attitudes. However, persistent stigmas and legal barriers remain significant obstacles. Addressing these challenges requires a multifaceted approach, encompassing policy reforms, awareness campaigns, and support systems that highlight the benefits of inclusive hiring. This research underscores the need for a balanced perspective that aligns societal reintegration goals with business interests, promoting a more inclusive and equitable job market for ex-convicts. The demographic data indicates that most employers are experienced, with 57% aged 30 to 49 and none aged 50 and 54% being male. All employers hold bachelor's degrees. Furthermore, 46% have over five years of service, and 43% are in managerial positions. Employers' perceptions of hiring ex-convicts were analyzed using various theoretical lenses. Attribution theory results showed a favorable perception, with a mean score of 3.80. Labeling theory indicated a rejection of negative stereotypes, with a mean score of 2.25. Conflict theory analysis revealed that educational background, professional licenses, job experience, and social standing influenced hiring decisions, with a mean score of 3.76. Education and work experience were crucial factors, with scores of 4.21 and 4.22, respectively.